THE PROBLEM OF MAN IN THE RELIGIOUS-PHILOSOPHICAL TEACHINGS OF IBN AL-ARABI - Mirzaev Akhrorjon Azamovich (Sciental Journals Publishing, 2025)
This scientific article briefly discusses Ibn al-Arabi's Sufi teachings, the main direction of his Sufi teachings, the natural structure of humans, the history of natural structure, his divine and religious views in the fields of philosophy and Sufism, his scientific works, and their essence.
Keywords: Islamic philosophy, Sufi philosophy, Great Sheikh, asceticism, philosopher, sage, Sufi orders, jurisprudential schools, truth, Pantheism, goodness, mysticism.